Internet Impact on the Insertion of Genitourinary Tract Foreign Bodies in Childhood. (11th September 2012) - Sinopidis, Xenophon; Alexopoulos, Vasileios; Panagidis, Antonios; Ziova, Alexandra; Varvarigou, Anastasia; Georgiou, George
Abstract : Foreign body self-insertion into the urethra is an uncommon paraphilia. Variety in object form, motivation, clinical presentation, complications, and treatment options is a rule. In childhood it is very rare, and it is attributed to curiosity or mental disorders so far. However, the internet impact on daily life of all age groups has created a new category of sexual behavior in childhood and adolescence, the "internet induced paraphilia." Such is the case of an electrical cable inserted in the urethra of a 12-year-old boy reported here, which is representative of this kind of impact.